Link between steroidogenesis, the cell cycle, and PKA in adrenocortical tumor cells. (15th January 2020) - Rizk-Rabin, Marthe; Chaoui-Ibadioune, Sabrina; Vaczlavik, Anna; Ribes, Christopher; Polak, Michel; Ragazzon, Bruno; Bertherat, Jerôme
Abstract: Adrenocortical tumors (ACTs) frequently cause steroid excess and present cell-cycle dysregulation. cAMP/PKA signaling is involved in steroid synthesis and play a role in cell-cycle regulation. We investigated, by cell synchronization in the different phases of the cell-cycle, the control of steroidogenesis and the contribution of PKA in adrenocortical cells (H295R and culture of primary pigmented nodular adrenocortical disease cells). Cells showed increased steroidogenesis and a maximal PKA activity at G2 phase, and a reduction at G1 phase. PRKACA overexpression, or cAMP stimulation, enhanced PKA activity and induced steroidogenesis in all synchronized groups but is not sufficient to drive cell-cycle progression. PRKAR1A inactivation enhanced PKA activity and induced STAR gene expression, only in cells in G1, and triggered cell-cycle progression in all groups. These findings provide evidence for a tight association between steroidogenesis and cell-cycle in ACTs. Moreover, PRKAR1A is essential for mediating the function of PKA activity on both steroidogenesis and cell-cycle progression in adrenocortical cells. Highlights: Modulation of steroidogenesis by specific cell cycle phases in adrenal cell tumors. PKA activity varied notably according to the stage of cell cycle in the H295R cells. Early effect of enhancing PKA activity appears to be critical for steroid excess. PRKAR1A mediated the function of PKA activity on both steroidogenesis and cell cycle.